Impactos generados por el camal municipal, sobre la calidad ambiental de la ciudad de Guadalupe, departamento de La Libertad – Perú. - Díaz Núñez, Gianella (2023)
The determination of how the Municipal Slaughterhouse impact the environmental quality in the city of Guadalupe, belonging to the region of La Libertad, was the purpose of this descriptive, exploratory, and non- experimental investigation. Likewise, this investigation included identifying the activities carried out in the mentioned slaughterhouse where it possibly causes impacts on the environment and/or society, in the same way, in the influence zone were identified the potential impactful factors of the environmental quality. The impacts were identified and evaluated by a qualitative matrix method proposed by Lina Bergere Leopold (CONESA 2010). The investigation also includes a microbiological and physiochemical analysis of the Municipal Slaughterhouse effluents, in turn, a survey was applied to determine the perceptions of the inhabitants around the slaughterhouse about the impacts caused by said establishment. The results showed that, in the city of Guadalupe, the impacts generated by this slaughterhouse, both in magnitude and importance, there are much higher compared to the positive impacts, with a final score of -3,015. The environmental factors than can be impacted by the municipal slaughterhouse and its activities are: (a) water quality, (b) water consumption, (c) air quality, (d) noise levels, (e) soil quality, (f) aquatic flora and fauna, (g) resident’s health, (h) landscape quality, (i) fishing-bathing and swimming and (j) agriculture. In Guadalupe, the analysis showed a chemical oxygen demand (COD) of 5,020 milligrams of diatomic oxygen per liter (mg/L); a biochemical oxygen demand (BOD)